PENGARUH PONDOK PESANTREN TERHADAP KEHIDUPAN SOSIAL MASYARAKAT DESA KAJEN KEC. MARGOYOSO KAB. PATI - A. Zaenurrosyid (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2018)
In the manner of have been only 63 H area with 4.388 population, Kajen turn out to be have santri totally ± 1 million from multi region. More new comers which is when bring a various social lives, included the one organization this is scope space pondok pesantren in the Kajen village. By virtue of information that have a researcher concerned social lives in the Kajen village. That talked about condition make displacement either or fusion in the social lives area this is partitions inter-pesantren and around of society. Turn up the floor show, more internet shop wich is self inductance cross cultural from multi region and then the bring by santri or santriwati. By virtue of this case, researcher interested to find out lives social describe society Kajen village about selfinduced impact, like that impact from positive sector although impact from negative sector.